Biocatalytic degradation of reactive blue 221 and direct blue 297 dyes by horseradish peroxidase immobilized on iron oxide nanoparticles with improved kinetic and thermodynamic characteristics. (January 2023) - Kalsoom, Umme; Khalid, Nasira; Ibrahim, Affaf; Ashraf, Syed Salman; Bhatti, Haq Nawaz; Ahsan, Zainab; Zdarta, Jakub; Bilal, Muhammad
Abstract: In present study, we describe the biodegradation of direct blue (DB) 297 and reactive blue (RB) 221 by immobilizing horseradish peroxidase (HRP) isolated from fresh leaves of Moringa Oliefera on iron oxide nanoparticles. Iron oxide nanoparticles were synthesized by co-precipitation method and showed a maximum immobilization efficiency of 87%. The surface topography of iron oxide nanoparticles was envisaged by scanning electron microscopy (SEM), results showed that magnetic nanoparticles (MNPs) were in the form of aggregates having size of 1 μm. Furthermore, immobilization was confirmed via functional group identification performed by Fourier transformed infrared spectroscopy (FTIR). Immobilization phenomena displaced the optimum temperature from 35 °C to 50 °C moreover, pH optima were altered from 5.0 to 7.0. V max and K m for free and immobilized HRP, were 303 U/mg and 1.66 mM and 312 U/mg and 1.94 mM, respectively. Enzymatic thermodynamic measurements (ΔH*, ΔS*, Ea, ΔG*) were also evaluated for immobilized HRP and its free counterpart. Optimum degradation of reactive blue (RB) and direct blue (DB) 297 with free and immobilized HRP was observed at pH 5 and at temperature 40 °C respectively. The removal efficiency of DB 297 and RB 221 with free HRP was 75% and 86% while with immobilized HRP was 81% and 92% respectively. Furthermore, biodegradation of reactive blue (RB) 221 and direct blue (DB) 297 with immobilized and free biocatalyst was also investigated by Fourier transform infrared spectroscopy (FTIR) by identification of groups involved in dye degradation. FTIR results confirmed the 100% degradation of dyes. Immobilized HRP retained significant catalytic activity after five consecutive cycles of dye degradation. In conclusion, Fe3 O4 nanoparticles are promising and environmentally friendly media for enzyme immobilization. Moreover, immobilized HRP showed more thermal stability, pH stability and higher dye degradation efficiency as compared to free HRP. Furthermore, the immobilized HRP, economically more convenient and easily removable from reaction media. Owing to its thermal stability, ease of separation from reaction media and reusability, the magnetically separatable immobilized HRP can be exploited successfully for treatment of dye contaminated textile effluents. Graphical abstract: Image 1 Highlights: Designing immobilized horseradish peroxidase-based magnetic nano-biocatalytic system. Surface characterization by SEM and FTIR techniques. Assessing biochemical and thermodynamic parameters (Ea, ΔH*, ΔG*, ΔS*). Robust biocatalytic degradation of textile dye pollutants by immobilized nano-biocatalyst. Recycling efficiency of magnetically separatable immobilized HRP for five cycles.